A prospective, self-controlled study of sub-plateau heart rate variability in healthy adults - Ye, Xianglin; Liu, Hao; Yang, Haixia; Zhang, Hongyang; Gong, Meiting; Duan, Zhen; Fu, Yan; Xiong, Shiqiang; Dan, Xiaoping; Pei, Haifeng (Frontiers in Physiology, 2024)
BackgroundThe low-pressure, hypoxic environment characteristic of high-altitude regions significantly affects the cardiovascular and autonomic nervous system functions of individuals, consequently impairing their sleep quality. Heart rate variability, a non-invasive indicator of autonomic nervous system activity and balance within the cardiovascular system, has not been thoroughly investigated in terms of its patterns during acclimatization and de-acclimatization phases for individuals traveling to and residing in high-altitude areas and its relationship with sleep stability.MethodsData was collected from 22 medical staff members who traveled from Chengdu to Yecheng, with measurements taken before leaving Chengdu, 1 week in Yecheng, 3 months in Yecheng, and 1 week after returning to Chengdu. The study analyzed changes in heart rate variability during acclimatization and de-acclimatization at 1,400 m above sea level. It also examined arrhythmia and sleep disorders based on circadian groups.Results1. Following 1 week of acclimatization to the sub-plateau environment of Yecheng, significant decreases were observed in SDANN, SDNN and SD2 indices compared to departure from Chengdu (P < 0.05). After 3 months of sub-plateau acclimatization, these indices significantly increased (P < 0.05). Upon returning to Chengdu and undergoing de-acclimatization for 1 week, these indices further significantly increased (P < 0.05). 2. During the period of sub-plateau acclimatization and de-acclimatization, significant changes were noted in average heart rate and minimum heart rate (P < 0.05), with the average heart rate showing a continuous decrease and the minimum heart rate exhibiting an initial increase followed by a decrease. No significant changes were observed in maximum heart rate or the incidence of arrhythmias (P > 0.05). 3. When stratified by day and night, the trends for SDANN, RMSSD, and TP were consistent with the overall trend at night (P < 0.05), but opposite during the day (P < 0.05). 4. During the sub-plateau acclimatization period, stable sleep duration was significantly reduced, and increased markedly after de-acclimatization, although it did not return to pre-acclimatization levels (P < 0.05).ConclusionAcclimatization to the sub-plateau environment of Yecheng affects the autonomic nervous system, heart rate, and sleep in healthy adults. De-acclimatization can ameliorate these effects. Furthermore, the impact of sub-plateau acclimatization on the autonomic nervous system exhibits a distinct circadian rhythmicity.